How champions think in sports and in life - Rotella, Robert J.; Cullen, Bob (New York Simon & Schuster, 2016)
A "guide to success in all aspects of life-- not just sports-- from business to relationships to personal challenges of every variety"--Amazon.com.
What LeBron James has in common with Pat Bradley -- Learning to be optimistic -- A confident self-image -- Respecting your talent -- Commitment, perseverance, and habit -- Dreams, goals, and process -- Being single-minded -- Learned effectiveness : the virtuous circle -- Nerves and the performance process -- Evaluating yourself -- Going through the fire -- Working hard, working smart -- When to heed the competition and when to ignore it -- When to be patient and when to be impatient -- Surrounding yourself with the right people -- Doing what you love or loving what you do? -- Sticking with your bread and butter -- Creating your own reality -- A life of going for it.
Keywords: Sports -- Psychological aspects; Athletes -- Psychology; Athletes -- Attitudes; Success -- Psychological aspects